2008
DOI: 10.1037/a0012949
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial deficits predict rate of cognitive decline in autopsy-verified dementia with Lewy bodies.

Abstract: Dementia with Lewy Bodies (DLB) is often characterized by pronounced impairment in visuospatial skills, attention, and executive functions. However, the strength of the phenotypic expression of DLB varies and may be weaker in patients with extensive concomitant Alzheimer’s disease (AD). To determine whether strength of the DLB clinical phenotype impacts cognitive decline, visuospatial and language tests were retrospectively used to predict two-year rate of global cognitive decline in 22 autopsy-confirmed DLB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 55 publications
2
69
1
Order By: Relevance
“…Since the cognitive scores might inform the clinical diagnosis, there is a potential circularity in such findings, and thus the current results provide additional support for the hypothesis that mild DLB is associated with a characteristic cognitive profile. Similar findings have also been reported in neuropathologically confirmed cases of endstage DLB [27] .…”
Section: Discussionsupporting
confidence: 77%
“…Since the cognitive scores might inform the clinical diagnosis, there is a potential circularity in such findings, and thus the current results provide additional support for the hypothesis that mild DLB is associated with a characteristic cognitive profile. Similar findings have also been reported in neuropathologically confirmed cases of endstage DLB [27] .…”
Section: Discussionsupporting
confidence: 77%
“…However, several studies employing CDT did not report significant differences in overall total score in LBD and AD patients [156,157], likely because of the complexity of the task (see Fig. 1), although at least two studies reported significantly lower overall scores in LBD versus AD patients [158,159].…”
Section: Drawing Disorders In Lewy Body Dementiamentioning
confidence: 98%
“…No 2-year decline in FTD Comparison AD-LBD Nervi [152] Figure copying LBD worse than AD Crowell [153] Figure copying LBD worse than AD Tiraboschi [154] Figure copying LBD worse than AD; no differences in pentagon copying Cahn-Wiener [156] CDT No differences in overall score, but more conceptual and planning errors in LBD Hamilton [157] Clock copying No differences, but lower scores predicted steeper decline in LBD Cagnin [158] CDT LBD worse than AD Palmqvist [159] CDT, cube copying LBD worse than AD Gnanalingham [162] CDT, clock copying No difference in CDT; LBD worse than AD in clock copying Ala [164] Pentagon copying LBD worse than AD Cormack [165] Pentagon copying LBD worse than AD Connor [166] Pentagon copying No difference Caffarra [167] Figure copying, No difference in figure copying, pentagon copying worse scores in LBD on an analytic scoring system for pentagon copying AD, Alzheimer's disease; VaD, vascular dementia; sVaD, subcortical VaD; FTD, frontotemporal dementia; bvFTD, behavioral variant of FTD; PA, progressive aphasia; LBD, Lewy body dementia; CDT, Clock drawing test; ROCF, copy of Rey's complex figure. Reference numbering follows the text.…”
Section: Drawing Disorders In Vascular Dementiamentioning
confidence: 99%
“…Similar studies have been performed concerning the association between the PCT or the CDT and cognitive function in patients with DLB and Parkinson's disease [25,26]. One study showed that DLB patients with low scores on the CDT had faster cognitive decline than DLB patients with high scores on the CDT [25].…”
Section: Discussionmentioning
confidence: 73%
“…One study showed that DLB patients with low scores on the CDT had faster cognitive decline than DLB patients with high scores on the CDT [25]. Another study showed that low scores on the PCT were associated with cognitive decline in Parkinson's disease [26].…”
Section: Discussionmentioning
confidence: 99%